MRI identification of pseudolesions in the distal tibia articular surface: frequency and diagnostic criteria - Arndt, Hanka; Germann, Thomas; Fischer, Wolfgang; Rehnitz, Christoph; Antón Jiménez, Alba; Weber, Marc-André (European journal of radiology, 2024)
Objective - Pseudolesions of joints are known as focal irregularities of chondral or subchondral bone in typical joint areas and occur frequent but without clinical relevance. This study aims to report the prevalence and describe MRI findings of a previously unreported chondral, mostly posterior located pseudolesion of the distal tibia, and to define criteria to distinguish it from pathologic osteochondral lesions, as well as from another known pseudolesion of this area - the so called “Notch of Harty”. - Material and methods - A tri-centric retrospective case-control study included a total of 2,428 patients with ankle MRI examinations performed over a period of 6 years. MRI scans were evaluated by three radiologists in consensus for any cartilage irregularity of the distal tibial articular surface. For this purpose, the tibial articular surface was divided into 9 topographic regions. Proton-density weighted, fat-suppressed sequences in sagittal and coronal acquisition were used to assess the postero-medial articular surface of the tibia. Imaging features such as size and localization of cartilage irregularity and/or a cortical mould as well as presence of associated edema and/or subchondral cysts were reported. Demographic data (sex, age, and weight) was also recorded. Clinical data comprised presence of pain, movement impairment, and concomitant pathologies. - Results - A total of 68 patients (34 male, 34 female) with a lesion of the distal tibia were identified that had a new pseudolesion (prevalence of 3%). These lesions occurred most frequently (50 out of 68, 74%) in the postero-medial distal tibia plafond and were more commonly detected in the age group of 9-30 years (47%). In 13 of these 68 cases, the cartilage irregularity was the sole lesion without subchondral abnormalities. By defining these cases as definite pseudolesions, the prevalence was 1% and their age distribution was similar to that of the 55 other lesions with subchondral changes. Here with 11 of the 13 cases the majority (85%) were seen in the posterior part, especially in the postero-medial part (55%) of the distal tibia. The size of the cartilage defect ranged from 1 to 7 mm, and the majority (69%) sized from 2 to 3 mm. In 36 of 68 patients, we have seen subchondral alterations such as edema and/or cysts in addition to cartilage irregularity. 66% (n = 45) of these changes were edema and 37% (n = 25) were cysts. None of these 68 new pseudolesions with or without subchondral changes needed surgical or arthroscopic intervention. In the radiological and orthopaedic reports, clinical symptoms such as pain or instability were never associated with our observed lesions and there was no significant correlation between the presence of motion-related pain and imaging findings of cartilage irregularity, subchondral edema, and subchondral cysts. Thirteen patients had MRI follow-up examinations. Here the lesions did not show any MR morphological changes or clinical deterioration. Besides the new pseudolesion, which occured mainly in the posterior part of the tibia surface, we observed the “Notch of Harty” with a higher prevalence (25%) in our patient cohort. The typical localization was in the antero-medial tibial articular surface, without any edema or cysts. There were no coincidences of patients with both a new pseudolesion and the “Notch of Harty” - Conclusion - A new pseudolesion is typically seen in the postero-central and postero-medial tibial articular surface with a prevalence of 3% and may be associated with only a small cartilage irregularity. In many cases, however, additional findings such as bone edema and/or an adjacent bone cysts were found, which impairs differentiation of these lesions from pathologic osteochondral lesions. The latter are obviously often associated with a larger cartilage defect and clinical symptoms. Due to the balanced age distribution between those pseudolesions with and without subchondral changes and the lack of clinical symptoms, we conclude that the here reported pseudolesions are not a predilection for a clinically manifest osteochondral lesion (OCL). At the very least, the apparent lack of clinical relevance increases the likelihood that we are dealing with a new true pseudolesion.
Online verfügbar: 26. November 2023, Artikelversion: 1. Dezember 2023
Gesehen am 02.04.2024